Reference collection amidst COVID-19 pandemic: fish, crustacea, and mollusc of rumphius expeditions deposited in Ambon, Indonesia. Issue 1 (1st June 2022) - Pitriana, P; Romdon, A; Islami, M M; Tala, D J; Nendissa, F; Basit, A
Abstract: Due to COVID-19, many scientists have to work remotely and have limited access to physical reference collections. This situation has highlighted that providing online digital content is considered one of the most effective solutions. To make materials of reference collection more accessible to scientists or researchers, we here report the Rumphius expeditions (1973 – 1980) materials to Indonesia that still remain at the Ambon Research Station or now become reference collection of Centre for Deep-Sea Research, LIPI-Ambon, Indonesia. The morphological analyses of fish, crustacea, and mollusc collected during the Rumphius expeditions revealed: 34 species from 23 different genera of fish; 21 species from 19 different genera of crustacea; and 60 species from 42 different genera of mollusc. This study demonstrates the value of reference collections as a resource in marine biology science and the important role of archivists in this current pandemic situation.